Analysis of medical surgical nursing specialist practice in neurological system disorder patients with primary cases of hemorrhagic stroke and non-hemorrhagic stroke using the Dorothea Orem theory model approach - Leniwita, Hasian; Sofiani, Yani; Rayasari, Fitrian; Yuniarsih, Winda; Untari, Diah (International Journal Of Community Medicine And Public Health, 2025)
Background: Hemorrhagic and non-hemorrhagic strokes are among the leading causes of neurological disability worldwide, often resulting in significant self-care deficits. Specialist medical-surgical nurses play a critical role in addressing these needs through structured, theory-guided interventions. Dorothea Orem’s self-care deficit nursing theory (SCDNT) offers a comprehensive framework to guide care for stroke patients experiencing functional dependency. Methods: This descriptive-analytic study used a retrospective case study approach to examine the application of Orem’s SCDNT in stroke care. The study was conducted at Gatot Subroto Army hospital and the Pusat Otak nasional hospital in Jakarta from October 2022 to May 2023. Data were obtained from three directly managed cases and 40 patient medical record summaries meeting inclusion criteria (hemorrhagic or non-hemorrhagic stroke, ≥6 days hospitalization, complete documentation). Structured reviews of nursing and physician records captured variables such as demographics, risk factors, national institutes of health stroke scale (NIHSS) scores, and nursing diagnoses. Nursing interventions were categorized using Orem’s care systems: wholly compensatory, partially compensatory, and supportive-educative. Descriptive statistics and thematic interpretation were used to analyze patterns and theory-practice alignment. Ethical clearance was not required due to the use of de-identified secondary data, though institutional permission was obtained. Results: The majority of patients were male (75%) and aged 51-60 years. Hypertension was the most common risk factor (40%). NIHSS scores most frequently ranged from 5-15, indicating moderate stroke severity. The dominant nursing diagnosis was ineffective cerebral perfusion (52.5%). Most patients required wholly or partially compensatory nursing systems based on their level of dependence and clinical status. Conclusions: Dorothea Orem’s theoretical model effectively supported the delivery of individualized, structured nursing care in stroke patients with neurological deficits. The use of wholly and partially compensatory systems aligned with patients’ functional limitations, enabling nurses to meet care needs, support recovery, and gradually enhance self-care capabilities. These findings underscore the relevance of theory-based practice in specialist nursing and its value in improving outcomes for stroke patients.